2007
DOI: 10.1002/adma.200601998
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Viscoelasticity and Residual Stress Effects on Nanoimprint Lithography

Abstract: The decay kinetics of polystyrene (PS) gratings are monitored by tracking the intensity of the first‐order laser diffraction peak as a function of annealing time. For low‐molecular‐mass PS (24 kg mol–1, blue circles), an exponential response suggests that the pattern decay is a surface‐tension‐ driven viscous flow. In high‐molecular‐mass PS (1007 kg mol–1, green circles) a complicated response includes a rapid elastic recovery, a power‐law creep, and a viscouslike flow (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
107
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 31 publications
3
107
1
Order By: Relevance
“…1͒. We found that the modulation amplitude decreases exponentially as observed previously 17,18,20 and that the relaxation rate decreases strongly when the thickness of the layer decreases.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…1͒. We found that the modulation amplitude decreases exponentially as observed previously 17,18,20 and that the relaxation rate decreases strongly when the thickness of the layer decreases.…”
supporting
confidence: 69%
“…This parameter is prominent in a number of numerical studies of embossing 15,16 but there is still a good deal of confusion over this issue. On the one hand, some studies of NIL reflow 17,18 completely neglect the direct impact of confinement on flow rate. On the other hand a model has recently been developed, based on the lubrication approximation 19 but its validity in realistic cases has not been assessed.…”
mentioning
confidence: 99%
“…[7][8][9] The capillary instability governing this rounding and decay can be described in terms of a Laplace pressure, P acting on the surface topography, f(x,y). The Laplace pressure 14 is given by the product of the surface tension g and the local curvature, k z f 00 (x,y).…”
mentioning
confidence: 99%
“…However, thermal cycling can lead to dimensional distortion and volume shrinkage of replicated nanostructures when there are sizeable differences in thermal-expansion coefficients between the printable layer and device substrate. [5,6] In addition, most low-molecular-weight organic layers used for plastic electronics show bad thermoplastic behavior, and unintended crystallization of the organic layer degrades the device performance of the organic material. [7] To overcome these problems, alternative approaches have been investigated, including i) introduction of new stamp materials or resists with low T g , such as spin-on glass (SOG), hydrogen silsesquioxane (HSQ), and oligomer compounds; [7][8][9] ii) reducing T g to close to room temperature by modification of the processing atmosphere, including CO 2 absorption and solvent vapor treatment; [10,11] and iii) development of nonthermal curing processes, such as step-and flash-imprint lithography, laser-assisted direct imprint, and free-volume contraction.…”
mentioning
confidence: 99%